PAMELA measurements of the boron and carbon spectra. (July 2015) - Mori, N; Adriani, O; Barbarino, G C; Bazilevskaya, G A; Bellotti, R; Boezio, M; Bogomolov, E A; Bongi, M; Bonvicini, V; Bottai, S; Bruno, A; Cafagna, F; et al.
Abstract: The satellite-borne PAMELA experiment is aimed at precision measurements of the charged light component of the cosmic-ray spectrum, with a particular focus on antimatter. It consists of a magnetic spectrometer, a time-of-flight system, an electromagnetic calorimeter with a tail catcher scintillating layer, an anticoincidence system and a neutron detector. PAMELA has measured the absolute fluxes of boron and carbon and the B/C ratio, which plays a central role in galactic propagation studies in order to derive the injection spectra at sources from measurements at Earth. In this paper, the data analysis techniques and the final results are presented.